High efficient organic solar cells - Heng, Jordan Hock Leong (Nanyang Technological University, 2021)
Organic Solar Cells (OSC) are currently attracting scientific and economic interest because it is an emergent photovoltaic technology for low-cost power production. Its main advantages lie within its flexibility, lightweight, and low cost. However, it has a lower power conversion efficiency (PCE) when compared to its inorganic counterpart, thus making it less reliable as a photovoltaic system.